Long-term, 13-year survival after immune cell therapy combined with chemotherapy for extensive-stage small-cell lung cancer: a case report - Liu, Tong; Wang, Heshuang; Kong, Qinglong; Wang, Haoyu; Wei, Haodong; Sun, Pengda (Frontiers in Oncology, 2024)
While the incidence of small-cell lung cancer is low, it has a poor prognosis. Patients with extensive small-cell lung cancer account for about 70% of all cases of small-cell lung cancer, with a median overall survival duration of 8-13 months and a 5-year overall survival rate of only 1%-5%. Herein, we report small-cell lung cancer diagnosed by bronchoscopic biopsy in an adult male patient in 2011. The patient had a clinical stage of cT2N2M1 and stage IV disease (i.e., extensive small-cell lung cancer). Still, he survived for 13 years through a combination of chemotherapy, radiotherapy, and cytokine-induced killer (CIK) immunocell thera. Comprehensive tumor markers, lymphocyte subsets, and lung CT images were obtained through long-term follow-up. After 12 cycles of chemotherapy (CE/IP regimen) and 5940cgy/33f radiotherapy, we found that the patient was in an immunosuppressive state, so the patient was given CIK cell therapy combined with chemotherapy. After 2 years of immunocell-combined chemotherapy, there were no significant changes in the primary lesion or other adverse events. In the 13 years since the patient's initial diagnosis, we monitored the changes in the patient's indicators such as CEA, NSE, CD4/CD8 ratio, and CD3+CD4+ lymphocytes, suggesting that these may be the factors worth evaluating regarding the patient's immune status and the effectiveness of combination therapy. In this case, CIK cell immunotherapy combined with chemotherapy was applied to control tumor progression. With a good prognosis, we concluded that CIK cell immunotherapy combined with chemotherapy can prolong patient survival in cases of extensive small-cell lung cancer, and the advantages of combined therapy are reflected in improving the body's immune capacity and enhancing the killing effect of immune cells.